Cascaded channel estimation technique for massive MIMO relay system - Ling, Y.L.D.; Chiong, Raymond; Zang, Z. (2018)
© Published under licence by IOP Publishing Ltd. This paper concerns with the cascaded channel estimation of massive multiple-input multiple-output (MIMO) relay system. In order to meet the increasing demands for high-speed wireless communication networks, massive MIMO has been recognized as one of the key technologies for the future fifth generation (5G) cellular networks. It is an advanced MIMO technique consists of a very large number of antennas at the base station and serves a smaller number of single-antenna users simultaneously. Basically, the idea of massive MIMO technique is to harvest all the advantages of conventional MIMO system in a much larger scale. To reap the benefits of massive MIMO in practice, an accurate estimation of the channel state information (CSI) is needed. In this paper, the relaying technique has been incorporated with massive MIMO system in order to increase system throughput and improve the coverage in cell-edge users. A relay node is placed in between transmitter and receiver to reduce the path loss and improve the spectral efficiency of massive MIMO system. Cascaded channel estimation technique for massive MIMO relay system is developed in this paper. The mean squared error (MSE) of the cascaded channel estimation for massive MIMO relay sytem is optimized to obtain accurate CSI.